CGIAR GENDER Impact Platform Newsletter, April-May 2022, issue 1 - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
In this issue, we share with you latest news from the CGIAR GENDER Impact Platform as well as updates on gender research from across CGIAR's research portfolio. We shine a spotlight on the importance of better research methods for maximum gender equality impacts. For example, tools for measuring women's empowerment must produce precise, comparable results to enable us to track progress toward women’s empowerment across projects, sectors and regions. Also a new CGIAR GENDER working paper offers guidance on how to integrate gender considerations in value chain development projects. Another highlight is a list of top 10 reads on gender and entrepreneurship.